Cluttering – the past and the present - Kaźmierczak, Monika (Papers in Linguistics, 2024)
Cluttering is still not a well-recognized speech fluency disorder, either in Poland or in the world. There are relatively few publications on this linguistic and communication phenomenon in Polish. The article presents a historical outline and contemporary attempts to explain the essence of cluttering based on literature and international classifications. It also focuses on the perspective of speech therapists and clutterers, who often use metaphors or analogies to illustrate the nature of cluttering and explain this phenomenon. This review presents and summarizes the current knowledge on cluttering, tracking changes in the perception of cluttering, and highlighting the importance of evidence-based academic analysis and practice in speech therapy.